Estudo dos efeitos antiangiogênicos da desintegrina-símile Alternagina-C (ALT-C) em células endoteliais (HUVEC), tendo como alvo a integrina α2β1 - Santos, Patty Karina dos (2020)
Angiogenesis is a crucial process in tumor progression, and it is mainly regulated by the vascular endothelial growth factor (VEGF) and its receptor, VEGFR2. Studies have shown that VEGF/VEGFR2 axis signaling is directly associated with functional responses of integrins in endothelial cells (crosstalk). Alternagin-C (ALT-C), a disintegrin-like protein from Bothrops alternatus snake venom, has high affinity for α2β1 integrin, interfering in cell adhesion, proliferation and migration, besides modulating angiogenesis in a concentration-dependent form by a not completely understood mechanism. Here we evaluate the antiangiogenic activity of ALT-C in human umbilical vein endothelial cells (HUVECs) associated or not with VEGF, as well as its interference in α2β1/VEGFR2 crosstalk. ALT-C was purified from B. alternatus venom and 1000 nM of the protein was tested in several in vitro experiments using HUVECs. ALT-C strongly inhibited HUVEC tube formation and decreased VEGFR2 and α2β1 protein levels. The disintegrin-like protein affected actin cytoskeleton, decreasing the number of cell filopodia, inhibiting HUVEC adhesion to collagen I and cell migration. ALT-C interfered in ERK 1/2, PI3K and FAK-Src/paxillin pathways, besides inducing autophagy, resulting in inhibition of the angiogenic process. Additionally, co-localization and surface plasmon resonance assays demonstrated that ALT-C interacts with α2β1 and VEGFR2, respectively, having a 10-fold higher affinity for the integrin. All these results suggest that ALT-C, after binding to α2β1 integrin, inhibits VEGF signaling by interfering in the α2β1/VEGFR2 crosstalk, which results in angiogenesis impairment. We conclude that ALT-C is a potential candidate for the development of antiangiogenic therapies for tumor and metastatic treatment.